HOW INFORMATION TECHNOLOGY IS TRANSFORMING ORTHODONTIC TREATMENT - Juan Rapheal Diaz Simoes; Ahmadi , Behnaz (Educational Research in Universal Sciences, 2023)
This article provides an overview of how information technology is transforming orthodontic treatment. It discusses the impact of IT on diagnosis, treatment planning, appliance design and fabrication, treatment monitoring and communication, and the patient experience. The article also includes a list of references for further reading.